Christina McPhee: A Commonplace Book (punctum books, 2017)
Christina McPhee’s ‘commonplace book’ draws from a palimpsest of handwritten notes, lists, quotations, bibliographic fragments, and sketches, from an artist whose voracious reading practice is a direct feed into her life and art — all set to a visual and textual design-as-score, as prominent writers on painting, media arts, performance, video installation and poetics engage with her ‘open-work’ practice. Christina McPhee’s images move from within a matrix of abstraction, shadowing figures and contingent effects. The tactics of living are in subterfuge, like the dazzle ships of camouflage in war. This ‘commonplace book’ develops a view of recent work in collaged paintings, drawings, photomontage and video installation, around themes of environmental transformation and ‘post-natural’ community.